2003
DOI: 10.1021/ic030226d
|View full text |Cite
|
Sign up to set email alerts
|

Electroswitchable Photoluminescence Activity:  Synthesis, Spectroscopy, Electrochemistry, Photophysics, and X-ray Crystal and Electronic Structures of [Re(bpy)(CO)3(C⋮CC6H4C⋮C)Fe(C5Me5)(dppe)][PF6]n (n = 0, 1)

Abstract: A novel heterobimetallic alkynyl-bridged complex, [Re(bpy)(CO)(3)(C[triple bond]C[bond]C(6)H(4)[bond]C[triple bond]C)Fe(C(5)Me(5))(dppe)], 1, and its oxidized species, [Re(bpy)(CO)(3)(C[triple bond]C[bond]C(6)H(4)[bond]C[triple bond]C)Fe(C(5)Me(5))(dppe)][PF(6)], 2, have been synthesized and their X-ray crystal structures determined. A related vinylidene complex, [Re(bpy)(CO)(3)(C[triple bond]C[bond]C(6)H(4)[bond](H)C[double bond]C)Fe(C(5)Me(5))(dppe)][PF(6)], 3, has also been synthesized and characterized. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(44 citation statements)
references
References 47 publications
1
43
0
Order By: Relevance
“…It was found that the reaction of organic 5 with 9 gave somewhat better yields than with 8 with 9. Desilyl-A C H T U N G T R E N N U N G ation of 11 with [nBu 4 N]F (Bu = butyl) afforded 12 in almost quantitative yield. On the other hand, the introduc-…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It was found that the reaction of organic 5 with 9 gave somewhat better yields than with 8 with 9. Desilyl-A C H T U N G T R E N N U N G ation of 11 with [nBu 4 N]F (Bu = butyl) afforded 12 in almost quantitative yield. On the other hand, the introduc-…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, the reaction of 13 with 2-methyl-3-butyn-2-ol (formation of 16) under typical Sonogashira cross-coupling conditions also gave 15 (Scheme 3). [15] Desilyl-A C H T U N G T R E N N U N G ation of 14 was achieved by addition of [nBu 4 N]F. The de-protection of the propargylic group in 16 was carried out with powdered potassium hydroxide in toluene. Both reactions produced 15 as a colorless solid in good yield.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations